Modalność aporetyczna. Wokół jednego wiersza Piotra Sommera - Telicki, Marcin (Wydawnictwo Naukowe UAM, 2013)
The author of this article analyzes and interprets Piotr Sommer’s meta-textual poem Czym mógłby być [What could it be]. The basic critical formula of “aporetic modality” is a property of language (which is improved in the poem) that reveals the impossibility of formulating clear hypotheses about writing poetry. And so, Sommer’s poem turns out to be a specific deconstruction of a poem – by speaking the poet conveys a message about the impossibility of speaking. The assertion becomes a doubt, and the poem, understood as a structure, exposes its non-constructive, and thus, maybe, its truly lyrical face
Aporetic modality. On Piotr Sommer’s poem